MODERN METHODS OF FORMING COMPETENCE IN SCHOOL STUDENTS IN WORKING WITH INFORMATION (American Journal of Research in Humanities and Social Sciences, 2024)
This article is devoted to modern methods of forming schoolchildren's competence in working with information, and analyzes the effectiveness of using innovative and interactive methods for working with information.